(untitled) (International Journal of Current Engineering and Technology, 2015)
The security feature of Windows has been the most crucial issue ever since the commencement of the Windows systems. Passwords produced to ensure security for files and folders themselves have disadvantages and drawbacks in them. In this research, the vulnerabilities and disadvantages hosted by passwords shall be studied and minimized. We shall also implement a Two Factor Authentication [T-FA] System in the process by conjugation of Bluetooth and Rijndael Encryption. Selection of Bluetooth as an authentication factor is due to that fact that it’s most commonly available and every Bluetooth device has its own unique MAC address. Rijndael Encryption on the other hand is an AES and is widely believed to be most beneficial Cryptographic Encryption Algorithm available. The implemented Two Factor Authentication [T-FA] system should not only take out the disadvantages of passwords but is also aimed at providing a user friendly security system.